Anticipated Exchange Rate Reforms - Flood, Robert (IMF Working Papers; Working Paper ;, 1992)
Exchange rate reforms in developing countries have often aimed at floating the exchange rate in an attempt to unify the official and parallel markets for foreign exchange. This paper examines the anticipatory dynamics associated with such reforms. The analysis shows that if the future unified exchange rate is more depreciated than the prevailing official rate, a pre - announced reform will lead to a depreciation of the parallel rate upon announcement and, during the transition period, a rising premium, an increase in the rate of reserve losses, and possibly to an output contraction and an appreciation of the real exchange rate.